Membangun Karakter Mahasiswa Indonesia Melalui Pendidikan Karakter - Fredy Yunanto; Ria Kasanova (Departement of Mathematics Education, 2023)
The character and morality of students must be maximally cultivated so that they are not only superior in the academic field but also in the non-academic field to support their identity in the midst of globalization. Therefore, instilling noble character in Indonesian students is the most urgent matter that needs immediate attention. Through this study, it is believed that concepts or tactics for fostering noble character among Indonesian students can be found. This research was carried out using a literature review, which requires the collection and assessment of sources and facts from published works such as books, journals, papers, and theses. Data collection uses semantic and symbolic reading techniques. Based on the research findings, character education must still be carried out in higher education in order to improve and cultivate noble character among students. Teachers are responsible for fostering student character and morals. Through outstanding lecturer lessons in an academic setting, students will emulate lecturers and look up to them as role models.